Curva de hemoglobina em um grupo de gestantes normais Hemoglobin curve in a normal pregnant women group - Pedro Augusto Marcondes de Almeida; Cyro Ciari Jr; Jair Licio Ferreira Santos; Arnaldo Augusto Franco de Siqueira (Universidade de São Paulo, 1973)
Através das dosagens de hemoglobina realizadas em várias épocas da gravidez, em 701 gestantes sem suplementação de ferro escolhidas por amostragem casual simples de um universo de 7050 no período de 1947 a 1969, foi construída uma curva com as taxas médias de hemoglobina, que evidenciou uma queda que atinge o máximo por volta do 7.° mês de gravidez e elevando-se a partir desta época. A partir dela foi construída uma curva operacional e discutida a sua importância no diagnóstico e conduta frente a anemia na gravidez. Through hemoglobin determinations made in various stages of pregnancy, in 701 pregnant women with no iron supplementation ad hoc chosen out of a number of 7050 in the period from 1947 to 1969, a curve was constructed with the average rate of hemoglobin, which gave evidence of a drop that reaches its maximum around the 7th month of pregnancy and rises from that moment on. From this a working graph was built up and then it was discussed its importance in the diagnostic and treatment in anemia in pregnancy.